Study on the wear characteristics of aluminium metal matrix composite with 15% Al2O3 and 20% Al2O3 - Chua, Swu Chun. (2008)
The objective of this dissertation was to study the wear characteristics and behaviour of aluminium metal matrix composite materials (MMCs), namely Duralcan 286 and Duralcan 284 as a pin material when mated against three types of dics materials.